DO LACTOBACILLI CHALENGE GARDNERELLA VAGINALIS BIOFILMS? - Gjatovska, Liljana Labacevska; Pavlovska, Kristina; Petrovska, Milena; Jankoska, Gordana (Journal of Morphological Sciences, 2020)
Bacterial vaginosis (BV) is a highly prevalent vaginal dysbiosis that has been linked to adverse pregnancy outcomes and enhanced transmission of sexually transmitted infections (STIs). Key characteristics of the disease process are thought to be depletion of vaginal  Lactobacillus  and overgrowth of anaerobes (often dominated by  G.vaginalis ) and a pHâ€‰>â€‰4.5. Currently, is consensual that BV also involves the presence of a dense, structured and polymicrobial biofilm, primarily constituted by  G.vaginalis  clusters, strongly adhered to the vaginal mucosal surface. Biofilms are communities of microorganisms attached to a surface and encased in a selfproduced polymeric matrix. Reduction of the adhesive and biofilm forming capacity activity of  G. vaginalis  bacteria by Lactobacillus  strains is a well-known and desired effect of strains for potential vaginal probiotic application. The objectives of the present study were to evaluate in vitro the effect of Lactobacillus on biofilm production by different species of G.vaginalis isolated from women with bacterial vaginosis (BV). A total of 36 isolates from women with BV identified as G.vaginalis   were tested for their biofilm-forming capacity as monocultures and in bacterial coculture with confirmed non-biofilm producing strain of Lactobacillus, in a ratio of 1:1 by microtiter plate assay. Lactobacillus  strain in our study was capable of interfering with the growth of  G. vaginalis  biofilms to different degrees.  According to the criteria for biofilm-forming ability, after 24-h incubation 25%, 28% and 22% of  Gardnerella  monocultures were strong, moderate and weak biofilm producers, compared to 5.5%, 14% and 33.5% of  Gardnerella + Lactobacillus cocultures, respectively. Our results indicate the potential of lactobacilli as probiotics, since they effectively reduced the adheration and biofilm formation of the tested Gardnerella species which is a well-known and desired effect of strains for potential vaginal probiotic application. Key words : biofilms, resistance, lactobacilli, genital.